TANTANGAN GURU DALAM MENERAPKAN MANAJEMEN KELAS IV.B DI SEKOLAH DASAR NEGERI 03 NABIRE - Elisa Oktaviani Br Tampubolon; Rivaldo Paul Telussa; Dominggus Paulus Situru (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze in depth the challenges faced by teachers in implementing classroom management in the learning process in Class IV.B of State Elementary School 03 Nabire. This study uses a qualitative approach with a descriptive research type to understand the phenomenon contextually in the elementary school environment. The research subjects consisted of the homeroom teacher of class IV.B as the main informant and the principal as a supporting informant. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis included data reduction, data presentation, and drawing conclusions. The results of the study indicate that teachers face two main challenges in classroom management, namely the diversity of student characteristics that affect behavior, discipline, and learning participation, and differences in student academic abilities that cause gaps in material understanding. Teachers have made various efforts such as implementing varied learning strategies, providing motivation, and individual guidance to overcome these challenges. The novelty of this study lies in the specific study revealing the dynamics of teacher challenges in classroom management in elementary schools in the Nabire area, which have unique social and learning characteristics. This research provides both theoretical and practical contributions to the development of more adaptive and effective classroom management strategies.